Beyond Mission: Willibrord as a Political Actor between Early Medieval Ireland, Britain and Merovingian Francia (690-739) - Summer, Michel (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2022)
The thesis reassesses the activity of the Northumbrian cleric Willibrord (658 739) on the continent between 690 and 739. Traditionally, Willibrord has been perceived as the first representative of a new wave of Anglo-Saxon missionaries, who initiated the Christianisation of the peripheral regions of the Frankish kingdom with the support of the Carolingian dynasty. In contrast, the thesis examines the development of Willibrord s network in Francia and detaches his activity from a missionary framework which anticipates the formation of the Carolingian Empire after 751. The thesis shows that Willibrord s rapid integration into the area between Utrecht and Trier was based on his ability to combine different political and ecclesiastical networks, ranging from Ireland to Rome, with each other. Through the foundation of churches and monasteries, the consolidation of ecclesiastical traditions from the Insular world and the continent, and his interaction with different communities across north-eastern Francia, Willibrord secured his position a political actor in the Merovingian world. However, the early Carolingians were but one of many groups who supported Willibrord between 690 and 739, and their relationship was not predetermined. Contrary to the traditional scholarly narrative, Willibrord s activity extended beyond his mission to Frisia and contributed to the formation of a new ecclesiastical landscape in Merovingian Francia long before the ascension of the Carolingians.
APPROVED
Keywords: Early medieval history; Christianisation; Mission; Merovingian history; Carolingian history; Willibrord